ISOLATION AND CHARACTERIZATION OF A BACTERIUM THAT DEGRADES PBSA - HEMASHENPAGAM.N,; LALI GROWTHER,; MURGALATHA. N,; VASANTHA RAJ.S,; SATHIYA VIMAL.S, (International Journal of Pharma and Bio Sciences, 2013)
Microorganisms isolated from soil samples were screened for their ability to degrade biodegradable plastics.Among them, the most active strain S-32, was selected as the best strain for degrading these plastics. From its phenotypic and genetic characteristics of S-32 was closely related to Pseudomonas aeruginosa which could degrade both solid and emulsified poly butylene succinate co adipate (PBSA).